PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN QUANTUM LEARNING MATERI SAINS - Pane, Akhiril (IAIN PADANGSIDIMPUAN, 2014)
This research is a kind of classroom action research (action research class) aims to change students' learning outcomes. The location of this study in SMPN1 Padangsidimpuan. There are three objectives are achieved in this research, namely: (i) the ability to think creatively taught students before using Quantum Learning in material science. (ii) application of learning with Quantum Learning can improve students' ability to think creatively in solving problems of science. (iii) Improving students' ability to think preatif as taught by Quantum Learning in solving scientific problems. Dilaksanakn research stages withÂ two cycles, each cycle consisting of 3 times face to face learning. Results of research conducted both in cycle I and II shows that there is an increase in student learning outcomes using quantum science learning materials